Single-cell transcriptomic analysis of allergen-specific T cells in allergy and asthma - Seumois, Grégory (Sci Immunol, 2020)
CD4(+) helper T cells (T(H)) and regulatory T cells (T(reg)) that respond to common allergens play an important role in driving and dampening airway inflammation in patients with asthma. Until recently, direct, unbiased molecular analysis of allergen-reactive T(H) and T(reg) cells has not been possible. To better understand the diversity of these T cell subsets in allergy and asthma, we analyzed the single-cell transcriptome of ~50,000 house dust mite (HDM) allergen-reactive T(H) cells and T(reg) cells from asthmatics with HDM allergy and from three control groups: asthmatics without HDM allergy and non-asthmatics with and without HDM allergy. Our analyses show that HDM allergen-reactive T(H) and T(reg) cells are highly heterogeneous, and certain subsets are quantitatively and qualitatively different in subjects with HDM-reactive asthma. The number of interleukin (IL)-9 expressing HDM-reactive T(H) cells is greater in asthmatics with HDM allergy compared to non-asthmatics with HDM allergy, and this IL-9-expressing T(H) subset displays enhanced pathogenic properties. More HDM-reactive T(H) and T(reg) cells expressing the interferon-response signature (T(H)IFNR and T(reg)IFNR) are present in asthmatics without HDM allergy compared with those with HDM allergy. In cells from these subsets (T(H)IFNR and T(reg)IFNR), expression of TNFSF10 was enriched; its product, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), dampens activation of T(H) cells. These findings suggest that the T(H)IFNR and T(reg)IFNR subsets may dampen allergic responses, which may help explain why only some people develop T(H)2 responses to nearly ubiquitous allergens.